2019
DOI: 10.1038/s42003-019-0646-5
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetylation orchestrates wound-induced transcriptional activation and cellular reprogramming in Arabidopsis

Abstract: Plant somatic cells reprogram and regenerate new tissues or organs when they are severely damaged. These physiological processes are associated with dynamic transcriptional responses but how chromatin-based regulation contributes to wound-induced gene expression changes and subsequent cellular reprogramming remains unknown. In this study we investigate the temporal dynamics of the histone modifications H3K9/14ac, H3K27ac, H3K4me3, H3K27me3, and H3K36me3, and analyze their correlation with gene expression at ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 85 publications
0
50
0
Order By: Relevance
“…It is generally realized that the acetylation neutralizes the positive charge of lysine side chains on histones and reduces its interaction with the negatively charged DNA backbone, and thus relax the chromatin structure and promote gene transcription [70,71]. Indeed, H3K4ac and H3K9ac are often associated with gene activation, thereby modulating numerous biological processes such as stress responses in higher plants such as model plant Arabidopsis [72][73][74]. Increasing evidence from studies in Arabidopsis revealed that histone acetylations such as H3K4ac and H3K9ac are usually connected with histone methylation including H3K4me3, simultaneously regulating gene expression [71].…”
Section: Histone Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally realized that the acetylation neutralizes the positive charge of lysine side chains on histones and reduces its interaction with the negatively charged DNA backbone, and thus relax the chromatin structure and promote gene transcription [70,71]. Indeed, H3K4ac and H3K9ac are often associated with gene activation, thereby modulating numerous biological processes such as stress responses in higher plants such as model plant Arabidopsis [72][73][74]. Increasing evidence from studies in Arabidopsis revealed that histone acetylations such as H3K4ac and H3K9ac are usually connected with histone methylation including H3K4me3, simultaneously regulating gene expression [71].…”
Section: Histone Modificationmentioning
confidence: 99%
“…Besides DNA methylation and histone modifications, chromatin structure and gene expression may also be affected by chromatin remodeling, a process that disrupts histone-DNA interactions resulting in the altered accessibility of specific DNA regions to transcription machinery [79,80]. Chromatin remodeling factor (CHR), including the SWI/SNF ATPases, the imitation switch (ISWI) ATPases, and the chromodomain and helicase-like domain (CHD) ATPases subfamilies, could mediate either the ATP-dependent chromatin remodeling or the posttranslational histone modifications [57,58,[73][74][75][76][77][78][79][80][81][82][83][84]. The ATP-dependent chromatin remodeling complexes could alter nucleosome composition, and positioning and thus regulate DNA accessibility and gene expression.…”
Section: Chromatin Remodelingmentioning
confidence: 99%
“…However, the direct link between the wound signal and WIND1 expression have remained elusive until recently. Latest studies have shown that wounding produces changes in the H3K9/14 and H3K27 acetylation state of key reprogramming genes such as WIND1, ERF113 or LBD16 [48]. Moreover, it has been described that the histone variant HISTONE THREE RELATED 15 (H3.15), which lacks the PRC2-targeted K27 residue, is quickly induced after wounding.…”
Section: Wound Signaling Regulates Tissue Regeneration Through Consermentioning
confidence: 99%
“…Many chromatin remodeling factors, including POLYCOMB REPRESSIVE COMPLEX 2 (PRC2) components and DNA methyltransferases MET1 and CHROMOMETHYLASE 2 (CMT2), are differentially regulated by cutting as well. Accordingly, it was shown that chromatin modifications undergo dynamic changes upon wounding and accumulation or loss of histone 3 lysine 4 trimethylation (H3K4me3), and lysine 9/14/27 acetylation (H3K9/14/27ac), dependent on HISTONE ACETYLTRANSFERASE OF THE GNAT FAMILY 1 and 3 (HAG1&3), is respectively correlated to transcriptional activation or repression [ 32 ]. Genes with high levels of these permissive histone marks before or shortly after wounding (such as WIND1 , ERF113/RAP2.6L, and LBD16 ) tend to be rapidly induced by cutting, whereas genes with H3K36me3 and H3K27me3 are less responsive to wounding.…”
Section: Cellular and Molecular Framework Of De Novo Shoot Organogmentioning
confidence: 99%